Right to health v. right to smoke during COVID-19 pandemic in Malaysia - Md Tahir, Farah Sherwani; Onn, NorHusna Emirah; Fauzi, Husna (Global Academic Excellence (M) Sdn Bhd, 2022)
The tobacco epidemic is one of the world's most serious public health threats, killing more than 8 million people each year. More than 7 million of those deaths are directly related to tobacco use, while approximately 1.2 million are related to non-smokers being exposed to second-hand smoke. The World Health Organization Framework Convention on Tobacco Control (WHO FCTC) was adopted by the WHO to control tobacco consumption and provide protection to society from being exposed to tobacco smoke or better known as second-hand smoke (SHS). A smoking ban in public places has been widely implemented across the globe. However, the implementation of the smoke-free law has been challenging for many countries as it is said to impeach constitutional rights areas. In Malaysia, the enforcement of the smoke-free legislation in January 2019 has sparked outrage among smokers as they alleged the smoke-free law is unconstitutional and against human rights. This article also finds that Malaysia needs to be proactive in implementing effective measures to secure public health because tobacco control is a major issue that requires stronger state action which if it fails, the government can be accountable for not protecting individuals' right to health comprehensively.